Analisis Pengaruh Lingkungan Kerja dan Pemberian Kompensasi terhadap Kinerja Karyawan CV Mum Indonesia - Logahan, Jerry M.; Tjoe, Tjia Fie; Naga, Naga (Binus Business Review, 2012)
Mum CV is a company engaged in the sale of bread. To increase sales of bread (performance) it needs to investigate the influence of work environment and compensation of employees. The method of analysis used in this study is descriptive, Pearson Regression, and Multiple Regression. The data were obtained from the employees performance by completing the questionnaires provided using Likert scale which was useful to determine the level of disagreement questions on the questionnaires. Results achieved in this study are the work environment has no significant influence on employees performance in CV Mum Indonesia, amounting to 0,068. Compensation has significant, no influence on employees performance in CV Mum Indonesia that is equal to 0,580 and there is a significant effect of 33.6%. Work environment and compensation have a significant impact on employees performance in CV Mum Indonesia. It is equal to 0,580 and there is a significant effect of 33.6%.